Stakeholders’ Awareness and Attitude Towards Inclusive Education in Philippine Elementary Schools - Capillo, Ronielen; Naanep, Nathaniel (Journal of Interdisciplinary Perspectives, 2025)
This study focuses on the relationship between stakeholders’ level of awareness and attitude towards IE in mainstream classrooms in the selected five (5) elementary schools in West Isulan District, Division of Sultan Kudarat, Philippines. The study used a comparative and descriptive-correlational research design, which involved a total enumeration of 611 respondents. Through a researcher-made and validated survey questionnaire, the study found that stakeholders were highly aware of the significance, difficulties, and policies, and expressed very positive attitudes regarding mindset, beliefs, and actions towards IE, which further indicates that there is a positive attitude towards those with impairments if there is awareness regarding IE. Meanwhile, using the LSD test, there is a notable distinction in the level of understanding and the level of attitude among the different stakeholders, with principals having the highest mean. However, although teachers have a very positive attitude towards IE, they still obtained the lowest mean because they only have a basic understanding of how to teach and understand children with needs, not in addressing students with emotional and behavioral difficulties. A significant correlation was found between awareness and attitude, underscoring the need for targeted professional development, especially for teachers to enhance understanding and better practice implementing IE.